Previsão de crescimento e tolerância à seca para migração assistida de procedências de Eucalyptus grandis W. Hill ex Maiden para o Brasil - Amaral, Waldir Avelino Delfino (2019)
The adaptation of a given seed source to other modified environments can be predicted by comparison of its current performance with the optimum predicted by models that evaluate the reaction norms of populations and their individuals and, consequently, phenotypic plasticity, therefore, to conjecture that the responses of the provenances to the climatic conditions of exotic environments can also be predicted by the estimates of the impact of the movement of provenances along environmental gradients within the range. Normally, in the reaction norms, the climatic variables more related to the drought and that suffer greater variations as a function of the latitude, are the temperature and the precipitation. Thus, these are independent variables, whereas adaptation and plant growth, which are the most limited characteristics of these independent variables, are dependent variables. Eucalyptus is an important supplier of raw material for various industrial purposes, which is directly related to the great variability of the quality of the wood of its various species / clones. Several of its species have adapted very well to Brazil's soil-climatic conditions and have become important suppliers of raw materials for the production of firewood, charcoal, pulp and paper. Eucalyptus grandis is the most cultivated forest species in Brazil, due to its productive potential and the characteristics of wood, which is used for pulp and paper production, fiber and agglomerate panels, biomass energy, domestic use and sawmill products . The objective of this study was to evaluate the reaction standards of different Eucalyptus grandis cultivars in the states of Minas Gerais and Espírito Santo, to evaluate the applicability of the methodology proposed by Pedlar and McKenney (2017) to predict growth responses of E . grandis W. Hill ex Maiden in assisted migration processes for Brazil and predict tolerance for analyzes of historical series of drought magnitude, according to studies by Mackee et al. (1993), occurring in areas of Australian provenances of E. grandis seeds and in crop areas in Brazil. The results showed that the origin of Coffs Harbor, at first was not apt to be cultivated in Viçosa, unlike Kyoqle that still presented the best optimum distance of growth. The Atherton origin could be cultivated in both Lavras and Viçosa. It is also necessary to discard Orara West SF, for these cultivation sites, despite the presence of dry spikes, the intensities of the droughts were well below Lavras and Viçosa. Also among the untested provenances Collombatti SF, Cherry Tree SF and MT Lindsay presented excellent optimal growth distance and dry history similar to Lavras and Viçosa, making them suitable for cultivation in these locations. Among the curves of the reaction standards, Atherton originated from the others, being the one with greater phenotypic plasticity.